FIGURE 1 in Systematic position of Neocrangon communis (Decapoda, Crangonidae) based on the features of larval morphology - Sedova, Nina; Grigoriev, Sergey (Zenodo, 2014)
FIGURE 1. Distributions of surveys in Northwestern Pacific used to Crangonid investigations: A—West Kamchatka shelf, B—Eastern Kamchatka, C—Western Bering Sea. Published as part of Sedova, Nina & Grigoriev, Sergey, 2014, Systematic position of Neocrangon communis (Decapoda, Crangonidae) based on the features of larval morphology, pp. 559-575 in Zootaxa 3827 (4) on page 560, DOI:10.11646/zootaxa.3827.4.7, http://zenodo.org/record/4920752